1998
DOI: 10.1345/aph.17409
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antipsychotics and Patient Care in State Hospitals

Abstract: State hospital services have, by and large, embraced the developments in pharmacotherapy of schizophrenia. Optimal use of these new agents in this population requires additional information on their relative efficacy in specific patient subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Consequently, the risk for serious relapse is likely to be manifested in divergent hospitalization rates among patients, depending on the type of antipsychotic treatment. Several studies have compared the ability of atypical and typical antipsychotics to prevent hospitalization, mainly in schizophrenia (16, 18, 20–22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the risk for serious relapse is likely to be manifested in divergent hospitalization rates among patients, depending on the type of antipsychotic treatment. Several studies have compared the ability of atypical and typical antipsychotics to prevent hospitalization, mainly in schizophrenia (16, 18, 20–22).…”
Section: Discussionmentioning
confidence: 99%
“…Several past studies, focusing mainly on patients with schizophrenia, have used incidence of hospitalization to evaluate various antipsychotic therapies (14–22). A number of these studies found hospitalization to be lower in patients treated with atypical antipsychotics than in those treated with typical antipsychotics.…”
mentioning
confidence: 99%
“…Several studies have compared the various antipsychotic therapies with respect to risk for hospitalisation (8)(9)(10)(11)(12)(13)(14)(15)(16). The present study investigated the relationship between hospitalisation and antipsychotic treatment within a Medicaid population with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%